The American Literature Scholar in the Digital Age - Amy E. Earhart and Andrew Jewell, Editors (University of Michigan Press, 2011)
The American Literature Scholar in the Digital Age, which features a wide range of practitioner-scholars, is the first of its kind: a gathering of people who are expert in American literary studies and in digital technologies, scholars uniquely able to draw from experience with building digital resources and to provide theoretical commentary on how the transformation to new technologies alters the way we think about and articulate scholarship in American literature. The volume collects articles from those who are involved in tool development, usability testing, editing and textual scholarship, digital librarianship, and issues of race and ethnicity in digital humanities, while also situating digital humanities work within the larger literary discipline. In addition, the volume examines the traditional structures of the fields, including tenure and promotion criteria, modes of scholarly production, the skill sets required for scholarship, and the training of new scholars. The American Literature Scholar in the Digital Age will attract practitioners of digital humanities in multiple fields, Americanists who utilize digital materials, and those who are intellectually curious about the new movement and materials.
English
Keywords: American literature--Research--Electronic information resources; American literature--Research--Methodology; American literature--History and criticism--Electronic information resources; American literature--Study and teaching--Electronic information resources; Literature and the Internet--United States; American literature--Study and teaching--Methodology